HOW DID WILLIAM J. MORGAN SHAPE THE ETHICS OF SPORT? (Kinesiology, 2022)
In this paper, I will argue that William J. Morgan had a decisive role in and influence on the shaping of contours and field divisions of the ethics of sport, which is a sub-discipline of the philosophy of sport. In the first part, I will use six Morgan’s edited anthologies on philosophy (1979, 1987, 1995) and ethics of sport (2001, 2007, 2017) to show that in them, Morgan develops and uses a fourfold division of the fields of the ethics of sport – (1) competition and fair play, (2) human enhancements, (3) gender issues, and (4) social issues. I will also argue that these four fields of Morgan’s division have become largely accepted within the discipline as a sort of standard. To provide the rationale for the claim, I will take seven different editions of the ethics of sport, which were most considered and accepted in the field (Parry & McNamee; R. Simon; J. Boxill; McNamee; Simon, Torres & Hager). I will show that basically the same field division has been used in them, while the few detected differences are just placing more emphasis on specific topics or issues from Morgan’s earlier fourfold division. Moreover, I will use different articles on the topic from sportsphilosophical literature to support my claims even further. Also, I will make a claim that the origin of Morgan’s division, as well as its strength, derives from the discipline itself or the course of the development that discipline has taken from the beginning. In the end of this part, I will deal with possible anticipated objections. In the final part, I will provide a critical overview of the Morgan’s division, point out detected problems and provide possible solutions.Key words: William John Morgan, ethics of sport, contours and fields divisions